TEACHING WRITING SKILL THROUGH DIARY ACTIVITIES - Desriani Nggolaon; Irnasari Ramba (BABASAL English Education Journal, 2022)
This research aims to find out whether diary activities can improve students’ writing skill or not. This research is also quantitative research using quasi experimental research design with non-equivalent control group design. The population of this research was student of SMPN 1 Luwuk grade VIII. The sample of this research was 50 students, 25 students from class VIIIa (experimental class) and 25 students from class VIIIb (controlled class). The instrument of this research was test, where it was divided into pre-test and post-test. Treatment was given after giving pre-test in experimental class for about six meetings. Five aspects were assessed in order to find out the result. They are content, organization, vocabulary, language use and mechanism. The result of shows that the t-test of 73.9644 was higher than the t-table of 1.6772 with a significance level of 0.05 with 48 degrees of freedom. Therefore, the hypothesis of “Diary writing can improve the writing skills of the eighth grade students of SMPN 1 Luwuk” is accepted. In conclusion, diary activities can be used to improve students’ writing skill at SMPN 1 Luwuk significantly.